Bariatric surgery emphasizes biological sex differences in rodent hepatic lipid handling. Issue 1 (December 2017) - Grayson, Bernadette; Gutierrez-Aguilar, Ruth; Sorrell, Joyce; Matter, Emily; Adams, Michelle; Howles, Philip; Karns, Rebekah; Seeley, Randy; Sandoval, Darleen
Abstract Background Eighty percent of patients who receive bariatric surgery are women, yet the majority of preclinical studies are in male rodents. Because sex differences drive hepatic gene expression and overall lipid metabolism, we sought to determine whether sex differences were also apparent in these endpoints in response to bariatric surgery. Methods Two cohorts of age-matched virgin male and female Long-Evans rats were placed on a high fat diet for 3 weeks and then received either Sham or vertical sleeve gastrectomy (VSG), a surgery which resects 80% of the stomach with no intestinal rearrangement. Results Each sex exhibited significantly decreased body weight due to a reduction in fat mass relative to Sham controls (p  < 0.05). Microarray and follow-up qPCR on liver revealed striking sex differences in gene expression after VSG that reflected a down-regulation of hepatic lipid metabolism and an up-regulation of hepatic inflammatory pathways in females vs. males after VSG. While the males had a significant reduction in hepatic lipids after VSG, there was no reduction in females.Ad lib -fed and fasting circulating triglycerides, and postprandial chylomicron production were significantly lower in VSG relative to Sham animals of both sexes (p  < 0.01). However, hepatic VLDL production, highest in sham-operated females, was significantly reduced by VSG in females but not males. Conclusions Taken together, although both males and females lose weight and improve plasma lipids, there are large-scale sex differences in hepatic gene expression and consequently hepatic lipid metabolism after VSG.